Thoughts and comments from the World Championships in Trondheim
Unless you live here in Norway, I don`t think it is possible for you to have read or watched as much about the XC worlds in Trondheim as I have in the last 2 weeks. For Norwegians, this is the World Series, Super Bowl and Woodstock rolled into one. Nearly 100,000 people were present either in the stadium or along the course during the 4 x 10 km men`s relay. All but about 100 of them appeared to be waving a Norwegian (or Finnish, or Italian) flag! Nordic skiing is alive and well here in Europe. Here are some impressions and thoughts I had along the way.